Tau Isoform-Driven CBD Pathology Transmission in Oligodendrocytes in Humanized Tau Mice - Zareba-Paslawska, Justyna; Patra, Kalicharan; Kluzer, Luca; Revesz, Tamas; Svenningsson, Per (Frontiers in Neurology, 2021)
The aggregation of abnormally phosphorylated tau protein in neurons and glia is a neuropathological hallmark of several neurodegenerative disorders, collectively known as tauopathies. They are further subclassified based on the preferential pathological aggregation of 3 carboxyl-terminal repeat domains (3R) and/or 4R tau. Corticobasal degeneration (CBD) is a rare neurodegenerative disorder classified as a 4R tauopathy. In the present study, we extended analysis of CBD-tau cell-type specific pathology transmission with 3R and 4R tau isoforms distinguishable changes. We used a humanized tau mouse line (hTau), which overexpress all six human tau isoforms in murine tau knockout background, and performed intrastriatal inoculation of control and CBD-tau enriched human brain homogenate. We showed that CBD-tau causes hyperphosphorylation of tau at Serine202 predominantly in oligodendrocytes. Next, we demonstrated the spread of tau pathology from striatum to the overlaying corpus callosum and further to contralateral side. Finally, we demonstrated that almost exclusive oligodendrocytes based transmission of hyperphosphorylated tau is reflected in their endogenous 4R tau isoforms expression and corresponds to subclassification of CBD as a 4R tauopathy. Additionally, we identified functional changes in oligodendrocytes reflected by myelin basic protein abnormalities upon CBD-tau inoculation. These changes were not observed in murine tau knockout mice lacking both human and murine tau. Our study presents not only in vivo tau isoform driven region- and cell-specific tau pathology, but also underline that tau pathology seeding and transmission might be oligodendrocytes based. These results, which need to be extended to more cases, give new insights into why tauopathies might vary greatly in both histopathological and neuroanatomical pattern.